Charting the future of queer studies in communication and critical/cultural studies: new directions and pathways. Issue 2 (3rd April 2021) - Atay, Ahmet
ABSTRACT: In this essay, I argue that while queer studies within communication and cultural studies must take a transnational and decolonizing turn to move away from solely white and US-centric ways of conceptualizing queer lives and experiences, it should also further theorize the role of mediation, new media technologies, and quick media applications in queer worldmaking.